Tricolored bats at a southern range edge exhibit partial migration northward in autumn - Lisa M. Smith; Jeffery A. Gore; Terry J. Doonan; Caitlin J. Campbell (Movement Ecology, 2022)
Abstract Background Animal migration is a widespread global adaptation by which individuals move in response to environmental conditions to reach more favorable conditions. For bats in temperate climates, migration and hibernation are often associated with each other when these bats must migrate to reach suitable overwintering sites. However, differences in movement across the geographical range of a species and the degree to which hibernation drives migratory behavior of bats in subtropical climates, where conditions may remain warm with available prey year-round, remains incomplete. Understanding the migratory strategies of subtropical bats during winter is of increasing importance as they are threatened by stressors such as disease and environmental change. Methods We evaluated migration patterns of tricolored bats (Perimyotis subflavus) in Florida, USA, through analysis of stable hydrogen isotope ratios of the fur. We inferred the summer geographic origins of the fur samples and estimated the minimum distance and likely direction traveled by hibernating individuals. We used linear models to examine whether hibernation region, colony size, and an individual’s sex affected the distance traveled. Results We sampled 111 bats hibernating at 40 sites and found that more than half (54.1%) of individuals were residents of the area in which they hibernated. We found that almost half of the sampled bats (43.2%) traveled from southern Florida to overwinter in North Florida. We also documented three individuals that traveled > 100 km from northerly origins, one of which had traveled an estimated minimum distance of 1382 km. We also found that tricolored bats moved farther to reach hibernacula in Northwest Florida and hibernacula with more populous colonies, with no difference in movement between sexes. Conclusions Our results indicate a pattern of northward autumnal movements of tricolored bats in the subtropical southeastern portion of their range. We suggest that bats are differentially constrained at the edge of their geographical range, resulting in movement contrary to what is expected. Even though we found that few (2.7%) bats moved into Florida from farther north, those migrants can potentially transfer the fungus that causes the deadly white-nose syndrome, which does not currently occur in the state. Our results support the characterization of tricolored bats as flexible partial migrators, with a rarely exercised capacity for long-distance movements.